Disability in the Irish Labour Market: Evidence from the QNHS Equality Module 2010 - MC GINNITY, FRANCES; WATSON, DOROTHY (The Equality Authority and the ESRI)
In 2010, working-age people with a disability were less than half as likely to be active in the labour market (36% compared to 77% of other adults) and had a considerably higher unemployment rate (22% compared to 16% of other adults) than those without a disability, according to a new report published today (Wednesday 16th January) by the ESRI and the Equality Authority. Evidence from EU data indicates that the employment rate of people with a disability is low in Ireland by European standards. Furthermore, people with a disability are also more likely to have experienced discrimination. In 2010, 19 per cent of working-age people with a disability had experienced discrimination in the preceding two years compared to 13 per cent of other working-age adults. But there have been improvements in the area of discrimination against people with a disability: there was a significant fall in the percentage of people with a disability who experienced discrimination between 2004 and 2010 (from 26% to 19%). This means that while people with a disability in 2010 were more likely than other adults to experience discrimination, the gap had narrowed compared to 2004. The results are based on new analysis of the CSO's Quarterly National Household Survey: Equality Module 2010, which asked over 16,800 adults in Ireland about their experience of discrimination in a range of different situations. This was combined with information on individuals' labour market status. These data were collected after the labour market entered deep recession and in the report they are compared with data from the Equality Module conducted in 2004 during the economic boom. The report focused on people with a disability of working age (over 1,000 people with a disability aged 18 to 64, excluding students).
PUBLISHED
Keywords: Irish labour market